2016
DOI: 10.1111/eve.12535
|View full text |Cite
|
Sign up to set email alerts
|

Combined surgical and radiotherapy treatment of a mandibular ameloblastic carcinoma in a pony

Abstract: Summary A 9‐year‐old Welsh Section D gelding was referred to an equine hospital for evaluation and computed tomographic (CT) imaging of a left mandibular swelling. An expansile mass, found within the left mandible at the level of the caudal 2 cheek teeth, was surgically debulked and histology of the lesion identified it as an ameloblastic carcinoma. Radiotherapy using 4 fractions of 800 cGy, 7 days apart, was subsequently undertaken. The pony made excellent clinical progression following treatment. Repeat CT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…10 The mandibular ameloblastic carcinoma in this report was successfully surgically debulked and treated with radiation therapy, which has also previously been reported in the horse. 23 Based on our review of the literature, ameloblastic fibromas have not previously been reported in horses. There are numerous reports in cats 12,15 and cattle.…”
Section: Discussionmentioning
confidence: 94%
“…10 The mandibular ameloblastic carcinoma in this report was successfully surgically debulked and treated with radiation therapy, which has also previously been reported in the horse. 23 Based on our review of the literature, ameloblastic fibromas have not previously been reported in horses. There are numerous reports in cats 12,15 and cattle.…”
Section: Discussionmentioning
confidence: 94%
“…Malignant variants of ameloblastoma are extremely rare in domestic animal species and have only been reported in three dogs (Jiménez et al ; Hatai et al ; Aydogan et al ) and two horses (De Cock et al ; Reardon et al ) to date. None of these cases were associated with metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…; Reardon et al . ), cementoma (Pirie and Dixon ), ameloblastic fibro‐odontoma (Knowles et al . ) and complex odontoma (Dubielzig et al .…”
Section: Introductionmentioning
confidence: 99%